Data Set for Reporting of Uterine Malignant and Potentially Malignant Mesenchymal Tumors: Recommendations From the International Collaboration on Cancer Reporting (ICCR). (22nd November 2022) - Nucci, Marisa R.; Webster, Fleur; Croce, Sabrina; George, Suzanne; Howitt, Brooke E.; Ip, Philip P.C.; Lee, Cheng-Han; Rabban, Joseph T.; Soslow, Robert A.; van der Griend, Rachael; Lax, Sigurd F.; McCluggage, W. Glenn
Abstract : The International Collaboration on Cancer Reporting (ICCR) seeks to produce standardized, evidence-based protocols for the reporting of tumors with the aim of ensuring that all cancer reports generated worldwide will be of similar high quality and record the same elements. Herein, we describe the development of the data set for the reporting of uterine malignant and potentially malignant mesenchymal tumors by a panel of expert pathologists and a single clinician and provide the commentary and rationale for the inclusion of core and noncore elements. This data set, which incorporates the recent updates from the 5th edition of the World Health Organization Classification of Female Genital Tumors, addresses several subjects of debate including which mesenchymal tumors should be graded, how to document extent of invasion, mitotic counts, and the role of ancillary testing in tumor diagnosis and patient management. The inclusion of elements is evidence-based or based on consensus of the expert panel with clinical relevance being the guiding standard.